2018
DOI: 10.1016/j.jpainsymman.2018.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Outcomes of Psychology Referrals in a Palliative Care Department

Abstract: Palliative care psychology services successfully integrated into an interdisciplinary palliative care department and rapidly grew in both inpatient and outpatient settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 31 publications
4
18
0
1
Order By: Relevance
“…In order to address these barriers, integrating psychosocial services into oncology care rather than it being presented as an optional and separate service may be essential. This is the current practice in palliative care at our institution, with high psychology service utilization in our inpatient and outpatient setting . Our intervention did not include psychoeducation to explain potential benefits of psychology services, which may impact acceptance, perception, and satisfaction of psychology services and should be considered in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to address these barriers, integrating psychosocial services into oncology care rather than it being presented as an optional and separate service may be essential. This is the current practice in palliative care at our institution, with high psychology service utilization in our inpatient and outpatient setting . Our intervention did not include psychoeducation to explain potential benefits of psychology services, which may impact acceptance, perception, and satisfaction of psychology services and should be considered in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were eligible if they were 18 years or older, proficient in English, had a diagnosis of advanced cancer defined as locally advanced, recurrent, or metastatic, and were of normal cognitive status as determined by the study recruiter based on the ability to understand the nature of the study and consent process. Our Supportive Care Center provides counseling onsite in the clinic, usually on the same day as the medical appointment, referred by medical staff to either three master's level counselors at no cost or three billable psychologists, depending on patient distress level . Patients who had previously received psychological counseling from one of our mental health providers and/or those suffering from severe symptom distress as assessed by nursing staff during the appointment such that it would significantly interfere with participation were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, comprehensive palliative care integrates psychosocial treatment. Trained mental health providers can not only encourage expression of emotions but also, when indicated, use sophisticated evidenced‐based approaches, including cognitive behavioral therapy and acceptance and commitment therapy, to address clinically significant distress . An interdisciplinary team approach enhances patient care and supports the medical team in challenging cases with regard to patients and families so that neither physical symptoms nor emotional suffering is neglected …”
Section: Introductionmentioning
confidence: 99%
“…Palliative care is a holistic approach of care, which can be integrated early in the disease trajectory, alongside active, curative treatment, [1] and aims to alleviate physical and non-physical symptoms of patients and their families [2][3][4][5][6][7]. Though physical symptoms may be more easily identified by healthcare professionals, patients and carers, non-physical symptoms can equally disrupt the patient and family's quality of life and cause suffering [8]. In a recent rapid systematic review of randomised controlled trials looking at effectiveness of psychological interventions to improve quality of life in people with long term conditions, authors found that all 6 included studies significantly improved at least one quality of life outcome immediately post-intervention and were maintained at 12-months follow-up in one out of two studies for each of the short-(0-3 months), medium-(3-12 months), and long-term (≥ 12 months) [9].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent rapid systematic review of randomised controlled trials looking at effectiveness of psychological interventions to improve quality of life in people with long term conditions, authors found that all 6 included studies significantly improved at least one quality of life outcome immediately post-intervention and were maintained at 12-months follow-up in one out of two studies for each of the short-(0-3 months), medium-(3-12 months), and long-term (≥ 12 months) [9]. In another study, Ann-Yi S and colleagues report that 24% of palliative care in-patients and 19% of palliative care out patients in a major cancer centre benefited from psychology services [8]. Also, psychological distress has been associated with greater physical symptom severity, suffering, and mortality in cancer patients [10].…”
Section: Introductionmentioning
confidence: 99%